Developing circularity of construction waste for a sustainable built environment in emerging economies: New insights from China - Bao, Zhikang (Developments in the built environment, 2023)
Properly handling the long-standing dilemma between economy and environment in emerging economies is a global conundrum. The dilemma is especially perceivable in the construction industry, where profuse construction waste generation always degrades their environment and prevents them from sustainably progressing to developed economies. This study starts from two case studies of Shenzhen and Suzhou in China combining site visits and semi-structured interviews, where both cases, deemed as exemplary emerging economies have successfully developed circularity of construction waste. From comparative case studies, general strategies on developing circularity of construction waste in emerging economies have been derived, including starting from developing recycling, harnessing smart technologies, implementing strong government intervention and economic incentive and adjusting degrees of internalized and externalized government intervention depending on corresponding development stages. This study provides a useful reference for policymakers of emerging economies to develop circularity of construction waste by deploying targeted strategies for a sustainable built environment. •Strategies for construction waste circularity in emerging economies are derived.•Emerging economies should start from recycling and harness smart technologies.•Implementing targeted government intervention and economic incentive are advised.•Emerging economies are implied on policymaking of construction waste circularity.•It contributes to developing a sustainable built environment in emerging economies.